Life-stage dependent response of the epiphytic lichen Lobaria pulmonaria to climate - Di Nuzzo, Luca; Canali, Giulia; Giordani, Paolo; Nascimbene, Juri; Benesperi, Renato; Papini, Alessio; Bianchi, Elisabetta; Porada, Philipp (Frontiers in Forests and Global Change, 2022)
Lichens are poikilohydric organisms, whose internal water content tends to reflect external humidity conditions. After drying, they can reactivate their metabolic activity through water vapor uptake or liquid water input. Thus, lichen water-related functional traits are important as they are involved in the duration of the hydrated period. Models predicting the effect of environmental conditions on lichens are based mainly on the presence or absence of adult thalli. Nevertheless, ecological conditions required by lichens might vary during their life cycle, for example during propagule establishment or in the first stages of thallus development. Little is known about the different ecological requirements at the different development stages in lichens. In this work, we measured water holding capacity (WHC) and specific thallus mass (STM) of adult and juvenile thalli of the model species Lobaria pulmonaria along a climatic gradient to constrain the process-based model LiBry. The LiBry model allows accounting for the productivity of lichens with different physiological strategies under various environmental conditions. We simulated the activity and performance of adult and juvenile thalli in 9 regions of Italy and Corsica. The model was used to test if adult thalli of L. pulmonaria have a higher survival probability due to their higher aerodynamic resistance. In the current climatic condition, the LiBry model predicts a higher survival probability of adults with decreasing absolute survival rates of both life stages with increasing temperature. Adult thalli also result in having higher active time, specific thallus mass, and relative growth rate. We discuss the main implications of our simulation outputs, provide future perspectives and possible implementations of the LiBry model.